Commensurations of Aut(F_N) and its Torelli subgroup - Bridson, M; Wade, R (Springer Nature, 2024)
For N ≥ 3, the abstract commensurators of both Aut(FN ) and its Torelli subgroup IAN are isomorphic to Aut(FN ) itself.